Impact of Flood on Bayelsa State, Nigeria: Causes, Consequence, and Management Strategies - Nwambuonwo, Jude Okeibunor; Atie, Ogheneovo Maureen; Reuben-Okoye, Mariam (PT. Riset Press International, 2025)
One of the most common and destructive environmental hazards in Nigeria has been flooding that has resulted in massive destruction of infrastructure, agriculture and human settlements. The geomorphological characteristics and the closeness of the Atlantic Ocean makes Bayelsa State, which is in the low-lying Niger Delta region, highly susceptible to floods. This paper will discuss the 2022 flood disaster that occurred in Bayelsa State, its physical and socioeconomic effects, the primary causes of the disaster, and some of the current measures taken with regards to flood management. The study is an empirical research based on the structured questionnaires, interviews and field observations conducted in seven communities across Bayelsa and Delta States, but also supported by secondary information, which presents multidimensional impacts of the flood. The findings noted that the flood swept away farmlands, animals, and households, displaced thousands of people, disrupted both transport and education and increased poverty and food insecurity. Results also suggest that ineffective drainage, level ground and lack of government preparedness are some of the factors that contributed to the disaster. The paper ends by giving recommendations on the need to actively manage river basins, to develop proper urban planning and to establish a good collaboration between the institutions to ensure the development of resilience against the occurrence of future floods.